Financing Virginia's Colleges. Current Operating Income and Expenditures 1970-71. State-Controlled Colleges and Universities - Finley, Donald J.; Virginia State Council of Higher Education, Richmond ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This document presents the 1970-71 data on the current operating income and expenditures of the state controlled colleges and universities in the state of Virginia. The report presents two basic approaches to analyzing the financial data. One provides the percentage relationship of each function to total educational and general income or expenditures; and the second shows the amount of income or expenditures per full-time-equivalent student for each function. The percentage analyses reflect the relative degree of support for a function compared to the support given other educational and general functions. Data indicating the income or expenditure per full-time-equivalent student can be used as a general basis for comparison of similar institutions. (HS)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Economics; Educational Finance; Financial Support; Higher Education; State Aid; State Colleges